Дослідження мережного ресурсу Honey Pot Plus - Корнієнко, Б.Я.; Бойко, Г.О.; Снігур, О.С.; Устимець, Ю.О. (Моделювання та інформаційні технології, 2010)
This paper describes the basic principles of HoneyPot. A brief overview of the
principles of operation and design of safety systems based on HoneyPot. Are
reviewed, weaknesses and shortcomings of HoneyPot, identified the main drawback of
HoneyPot. We present the modifications of HoneyPot using a plugin which solves the
main disadvantage of HoneyPot – it’s passive.